Representation of Symbolic Metaphors in Minangkabau Proverbs - Yuniseffendri Yuniseffendri; Riki Nasrullah (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
This study examines the representation of figurative symbols in Minangkabau proverbs using a discourse analysis approach to understand the symbolic relationship between language, culture, and environment in the oral tradition of the Minangkabau people. The study focuses on identifying forms of figurative symbols based on Michael C. Haley's Theory of human perception space, which includes the categories of human, living, and terrestrial. This research used a qualitative descriptive method through content analysis of 1000 Minangkabau proverbs by Idrus Hakimy as well as employed field observations. The analysis was carried out by mapping figurative symbols into nine categories of human perception and interpreting their meanings in a sociocultural context. The results showed that the human Category dominates with a proportion of 42.7%, followed by the living category (16.1%), while the terrestrial Category only accounts for 0.9%. Theoretically, this study expands the application of Haley's perception framework in the local Minangkabau context, revealing the close interaction between human perception, ecological experience, and cultural wisdom. Practically, this study confirms the role of proverbs as a medium for preserving local wisdom values and a means of cultural education. Thus, Minangkabau proverbs have been functioned as a cognitive archive of ecological culture that preserves, passes on, and strengthens the community's cultural identity amid changing times.